The Influence of Substituent Orientation on the Photovoltaic Performance of Phthalocyanine‐Sensitized Solar Cells. Issue 13 (17th February 2016) - Tejerina, Lara; Martínez‐Díaz, M. Victoria; Nazeeruddin, Mohammad Khaja; Torres, Tomas
Abstract: Phthalocyanines (Pcs) are used as sensitizers in dye‐sensitized solar cells (DSSCs) because of their stability and intense absorption in the red and near‐IR regions. Impressive progress has been made in photovoltaic efficiencies by introduction of bulky peripheral substituents to help suppress macrocycle aggregation. To reach benchmark efficiencies reported for other related dyes, new designs need to be explored. Single carboxy‐ZnPc regioisomers substituted at the non‐peripheral positions by rigid aryl groups have now been studied, which has shed light on the influence of steric hindrance and/or orientation of the substituent around the anchoring group on the photovoltaic response. The regioisomer bearing the aryl group far away from the anchoring group produces a more effective sensitization of the TiO2 films and higher short‐circuit photocurrent density ( J sc ). Taking advantage of the good photovoltaic performance in the near‐IR region of this ZnPc, it was combined with another appropriate dye for panchromatic sensitization of the mesoporous photoelectrode and an increase of the overall device efficiency. Abstract : Orientation matters : Different regioisomers of a carboxy‐ZnPc substituted at the non‐peripheral (α) positions by rigid aryl groups have shown a distinct photovoltaic response, which has been correlated with the steric hindrance and/or orientation of the substituent around the anchoring group.